Inducing apoptosis in acute myeloid leukemia; mechanisms and limitations - Zahra Koolivand; Farbod Bahreini; Elham Rayzan; Nima Rezaei (Heliyon)
Acute myeloid leukemia is the expansion of leukemic stem cells which might originate from a stem cell or a progenitor which has acquired self-renewal capacity. An aggregation of leukemic blasts in bone marrow, peripheral blood, and extramedullary tissue will result in acute myeloid leukemia. The main difficulty in treating acute myeloid leukemia is multidrug resistance, leading to treatment failure. This unfortunate phenomenon is practically elevated because of apoptosis inhibition in tumor cells.Two general apoptotic pathways are the Bcl-2 regulated pathway (the intrinsic pathway) and the death receptor pathway. Deficiencies in each of these apoptotic pathways can cause the usual resistance mechanism in this disease. This article reviews and highlights different antiapoptotic pathways, currently-used treatments, and new findings in this field, which may lead to the development of treatment methods for acute myeloid leukemia.